ANALISIS PERILAKU TERLAMBAT PADA PESERTA DIDIK SMP NEGERI 2 SUNGAI RAYA - Syarifah Runika Umaria; Yuline Yuline; Purwanti Purwanti (Universitas Tanjungpura, 2019)
AbstractLate habit is an action of comming to a place or an event past the agreed time. Thishappens because the school is less firm in implementing the existing rules and as the form of students’ indiscipline. Every student in SMP Negeri 2 Sungai Raya is expected to have a disciplined attitude but in fact, there still can be found late students everyday. In general, this study aims to obtain an overview of